Spatially homogeneous bulk viscous fluid models with time-dependent gravitational constant and cosmological term - Verma M.K.; Ram S. (My University, 2025)
Einstein's field equations with variable gravitational and cosmological constants are considered in the presence of bulk viscous fluid for Bianchi types-II, VIII and IX space-times by assuming conservation law for energy-momentum tensor. Exact solutions of the field equations are obtained using the conditions that (1) the shear scalar is proportional to scalar expansion (2) the bulk viscous coefficient is proportional to some power of the energy-density and (3) the comic fluid obeys the barotropic equation of state. The physical interpretation of the corresponding cosmological models of the universe are discussed. It is shown that the models are consistent with the recent observation on cosmology.